Elimination of glufosinate ammonium from aqueous solution with hollow fiber supported liquid membrane and mathematical modeling - Hinoon S. (2023)
A hollow fiber supported liquid membrane (HFSLM) was used to extract and eliminate glufosinate ammonium from aqueous solution using TOA (tri-n-octylamine) in hexane and sodium hydroxide (NaOH) as carrier and stripping phase, respectively. Maximum extraction (∼76%) and stripping (∼75%) were achieved by feed solution at pH 1.0, temperature 60 °C, TOA concentration 6% (v/v) and NaOH concentration 1.0 M. The developed mathematical model exhibited high precision when predicting the concentration of glufosinate ammonium in raffinate solution and extraction percentage under different feed flow rates, with correlation coefficient (R 2) 0.9863.